Introduction of fibrin adhesive system (tissucol) in periodontal surgery; part II : clinical pocket reduction and attachment regeneration (Mustansiria Dental Journal, 2005)
The major goal of periodontal therapy is to eliminate the periodontal pockets and `to create a connective tissue attachment. Forty two patients with periodontal pocketssubdivided into 2 groups, Tissucol group, 21 patient were treated surgically withintroduction of` Tissucol bioadhesive material, other 21 patients were also treatedsurgically their flaps were sutured according to the traditional suture technique. Theresult showed that there were a significant gain in the pocket depths reduction andattachment levels in both groups, but that of Tissucol group is superior than that ofsuturing group. The patients were followed for six months, the stability of the gain inTissucol group still significant, while that of suturing group showed a significant loss inpocket depth reduction and attachment level during the six months of follow up. Theresult suggested that the tissucol help in creation of connective tissue attachment andpreventing the invasion of epithelial growth. The role of oral hygiene were also taken inconsideration , as long the oral hygiene kept in healthy state level as the gain in pocketdepth and attachment level maintained stable .